The Influence of TikTok Shop’s UI/UX on Fashion Purchase Intention Mediated by Student Trust - Romanus Mando Fransius Silaen; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Journal of Strategic Marketing and Innovation, 2025)
This study aims to investigate the influence of User Interface (UI) and User Experience (UX) on Fashion Purchase Intention among university students, with Student Trust serving as a mediating variable. Utilizing the Stimulus-Organism-Response (SOR) framework, this research employed a quantitative approach through an electronic survey distributed to 120 active university students in Indonesia who utilize TikTok Shop. Data analysis was executed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The empirical results demonstrate that both UI and UX exert a positive and significant influence on Student Trust and Purchase Intention (p<0.05). Notably, UX was found to be the most dominant driver of Purchase Intention (β=0.510), indicating that functional efficiency outweighs aesthetic design in finalizing buying decisions. Furthermore, Student Trust significantly validates Purchase Intention; however, the mediation analysis revealed that trust does not function as a significant mediator in this model, suggesting that technical stimuli drive purchase intent directly. These findings imply that social commerce platforms should prioritize operational fluidity and transactional security to sustain high conversion rates among digitally native consumers.